Factors Related to Students’ Psychosocial Problems during Covid-19 Pandemic - Emilia Puspitasari Sugiyanto; Candra Hadi Prasetyo; Wijanarko Heru Pramono (GLOBAL HEALTH SCIENCE GROUP, 2020)
COVID-19 pandemic cause various burdens, not only social, teaching and learning restriction but also financial problem. These problem affect the society particularly students which manifest as psychosocial symptom including insomnia, anxiety, irritability, fatigue however, the factors associate with these symptoms remains unclear. Thus, this study aims to analyze the factors associate with psychosocial problems of students during Covid-19 pandemic. This study was conducted on 101 students using qualitative methods with a cross sectional approach. The results showed that the average age of students was 20.11 years. Most of the correspondent was female (93.1%) with a small proportion of male (6.9%). The respondent mostly living in the city (54.5%) and in a boarding house (63.4%) while only a few of them live with their parents (36.6%). The stress level evaluation showed that there are 50 students experienced stress (49.5%). The gender significantly becomes a factor in inducing stress due to the hormonal system. Hormonal system affect their emotional condition result in the increased of stress level.